Platelet Factor 4 (PF4) Release during Human Platelet Aggregation in Diabetic Patients - Chmielewski, J; Farbiszewski, R (Thrombosis and Haemostasis, 1970)
The release of platelet factor 4 during platelet aggregation was investigated in diabetic patients. We observed an increased release of platelet factor 4 in diabetic patients.The authors suggest that the increased release of platelet factor 4 may play an essential role in pathogenesis of thromboembolic complications in diabetes mellitus.